How Does the Narrowing of Eligibility Criteria Affect Enrollment in Part C Early Intervention?. Issue 1 (January 2017) - Elbaum, Batya; Celimli-Aksoy, Seniz; Marshall, Jennifer T.; Berkovits, Michelle D.
Abstract : In recent years, many states have narrowed their eligibility criteria for participation in the IDEA Part C early intervention (EI) program for infants and toddlers with or at risk for developmental delays. However, there is scant research on the effects of such a policy change on the population of children served or on the timing of children's access to EI services. Using data from an EI program serving a diverse, urban population in a large southeastern state, we compared characteristics of children who enrolled in EI the year before ( n = 432) and the year after ( n = 399), the state adopted more restrictive eligibility criteria for its EI program. Results indicated that following the policy change, children served in the program represented a smaller percentage of the resident birth-to-3 population; a smaller proportion of children enrolling in EI had mild delays; and children were 1.5 months older, on average, when they enrolled in services. The findings not only provide evidence that the narrowing of eligibility criteria achieved the intended effect of reducing EI enrollment but also raise concerns that the new policy may delay access to needed services for children with emergent developmental delays.